Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Macroprudential Policy Framework. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for the Netherlands on the macroprudential policy framework. The authorities have strengthened the institutional arrangement for macroprudential policy by enhancing the Netherlands Bank's legal mandate and establishing the Financial Stability Committee, but there is room for improvement. The authorities' analysis of systemic vulnerabilities is sophisticated and timely. The authorities have been using the range of macroprudential instruments at their disposal, but further tightening will be necessary to contain a potential buildup of systemic risk in the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet